Marx's analysis of ground-rent: Theory, examples and applications - Deepankar Basu (University of Massachusetts, Department of Economics, 2018)
This paper offers a unified analytical treatment of Marx's theory of ground-rent, building on the analysis that is available in Volume Three of Capital. Since ground-rent is a transformation of surplus profit generated in agriculture, the main argument is developed in two steps. In the first step, I derive results on the existence of surplus profit in capitalist agriculture in the absence of landed property. In the second step, I used these results on surplus profit to arrive at the total ground-rent that is appropriated by the owners of land, and also decompose it into the three components that Marx highlighted: absolute rent, differential rent I, and differential rent II. I argue that the power of Marx's analysis lies in the fact that it can be generalised far beyond the domain of agriculture, which he had analysed, and can illuminate the emergence of rent in any system of capitalist commodity production that uses privately owned nonproduced resources that is limited in quantity. Hence, Marx's analysis of ground-rent can be used to investigate many interesting issues in contemporary capitalism.
Keywords: B51; 330; ground-rent; surplus value; Marx